Advance Care Planning in German General Practice: A Longitudinal Qualitative Study on Patients' Expectations and Experiences - Schmidt, Alexandra; Weckbecker, Klaus; in der Schmitten, Jürgen; Götze, Kornelia; Mortsiefer, Achim (Health expectations : an international journal of public participation in health care and health policy, 2025)
ABSTRACT Background Advance care planning (ACP) empowers individuals to make informed decisions about future medical care. While research has focused on patients with advanced chronic or terminal conditions, there remains a notable gap in understanding the perspectives and experiences of ambulatory individuals who proactively engage in ACP. Objective To explore ambulatory patients' perspectives on and experiences with facilitated ACP provided by trained professionals in German general practices, focusing on the expectations, motivations and outcomes of the ACP process. Design Longitudinal qualitative design using semi‐structured telephone interviews, conducted before, immediately after and 12 months after ACP facilitation. Interviews were analysed using thematic qualitative text analysis by Kuckartz. Setting and Participants Interviews were conducted with eight German patients (six females and two males; mean age: 63.6 years; frailty score from 1 to 5) in two general practice settings. Results Participants valued comprehensive advance directives (ADs) and structured ACP conversations in general practice. Key motivators for seeking ACP facilitation were maintaining autonomy and reducing family burden. Trustworthy discussions with professional facilitators, structured guidance and clear communication, particularly involving healthcare proxies, were essential for a satisfying ACP process. Despite expressing a prior interest in discussing care preferences, some participants had not yet initiated these conversations. Conclusions ACP facilitation enables patients to articulate their values and healthcare preferences, supporting decision‐making and reducing uncertainty. Integrating structured ACP discussions into routine primary care could enhance patient autonomy and preparedness. Future research should explore strategies to optimise ACP implementation and assess its long‐term impact on patient outcomes. Patient or Public Contribution Stakeholder and patient involvement is a crucial aspect of empowering research subjects and improving study feasibility and relevance. In this study, stakeholders such as experts in the field of ACP (one female GP and two male GPs), other GPs and patients were involved as an expert panel in a stepwise participatory approach. The process involved training in ACP facilitation for AS before conducting the study, expert panel meetings to identify research gaps and prioritise research topics, focus group discussions to conceptualise study design and data collection procedures, as well as the development of interview guidelines and data analysis. A patient advisory board (seven females and four males; age: 36–78 years with chronic illnesses) associated with the Institute of General Practice and Primary Care (iamag) was also involved in creating the interview guidelines (guidelines can be found in Appendix 2–4). Trial Registration German Clinical Trial Register (DRKS) (ID: DRKS00027368; date of registration: April 2023; URL: https://www.drks.de/DRKS00027368).